Costimulation of soil glycosidase activity and soil respiration by nitrogen addition. (28th July 2016) - Chen, Ji; Luo, Yiqi; Li, Jianwei; Zhou, Xuhui; Cao, Junji; Wang, Rui‐Wu; Wang, Yunqiang; Shelton, Shelby; Jin, Zhao; Walker, Laura M.; Feng, Zhaozhong; Niu, Shuli; et al.
Abstract: Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration (SR). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR. The links between soil extracellular enzymatic activities (EEAs) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEAs and SR to elevated N. Nitrogen addition significantly increased glycosidase activity (GA) by 13.0%, α ‐1, 4‐glucosidase (AG) by 19.6%, β ‐1, 4‐glucosidase (BG) by 11.1%, β ‐1, 4‐xylosidase (BX) by 21.9% and β ‐D‐cellobiosidase (CBH) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios (RRs) of GA were positively correlated with the SR‐RRs, even when evaluated individually for AG, BG, BX and CBH. This positive correlation between GA‐RR and SR‐RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEAs to various global change factors and their implications for ecosystem functions.